Evaluating P-NET message's response time with fixed priority queuing at application process level - Tovar, Eduardo (2014)
P-NET is a multi-master fieldbus standard based on a virtual token passing scheme. In P-NET each master is allowed to transmit only one message per token visit. In the worst-case, the communication response time can be derived considering that, in each token cycle, all stations use the token to transmit a message. In this paper, we define a more sophisticated P-NET model, which considers the actual token utilisation. We then analyse the possibility of implementing a local priority-based scheduling policy to improve the real-time behaviour of P-NET.